What to expect that you're not expecting: A pilot video education intervention to improve patient self-efficacy surrounding discharge medication barriers. (December 2019) - Sinha, Sanjai; Dillon, John; Dargar, Savira Kochhar; Archambault, Alexi; Martin, Paul; Frankel, Brittney A; Lee, Jennifer Inhae; Carmel, Amanda S; Safford, Monika
The objective of this study was to test the feasibility of video discharge education to improve self-efficacy in dealing with medication barriers around hospital discharge. We conducted a single-arm intervention feasibility trial to evaluate the use of video education in participants who were being discharged home from the hospital. The scores of pre- and post-intervention self-efficacy involving medication barriers were measured. We also assessed knowledge retention, patient and nursing feedback, follow-up barrier assessments, and hospital revisits. A total of 40 patients participated in this study. Self-efficacy scores ranged from 5 to 25. Median pre- and post-intervention scores were 21.5 and 23.5, respectively. We observed a median increase of 2.0 points from before to after the intervention (p = 0.046). In total, 95 percent of participants reported knowledge retention and 90 percent found the intervention to be helpful. Video discharge education improved patient self-efficacy surrounding discharge medication challenges among general medicine inpatients. Patients and nurses reported satisfaction with the video discharge education.